Metal Biology Takes Flight: The Study of Metal Homeostasis and Detoxification in Insects - Stephanie E. Mohr; David W. Killilea (Frontiers Media SA, 2021)
Metals such as copper, iron, manganese, and zinc are clearly required for proper metabolism and development, while imbalances can lead to systemic dysfunction and disease. As a result, organisms have evolved complex genetic systems for the regulation of metal levels, including import, export, and sequestration of metals within cells and sub-cellular compartments. The study of metal biology in insects has the potential to greatly expand our understanding of metal biology. The results of such studies might point to new possible therapeutic interventions for neurological and other human diseases, as well as new strategies for insect disease vector control. The articles collected in this Research Topic comprise review and original research on metal biology in insects.